The Status Quo and Attribution of Wildlife Crimes: A Study of Cases in China From the Perspective of Ecological Economic Ethics - Zhang, Zhongmin; Zeng, Yuting; Xie, Danqi (Frontiers in Public Health, 2021)
The COVID-19 pandemic, which has ravaged the world, has led to a rethinking of the relationship between humans and nature and the clichés of the economic-centered model. Thus, the ecological economy has been reviewed, especially from an ethical worldview. This paper uses statistical methods to retrieve and categorize 3,646 wildlife crime cases for analysis and quantitative research. It adopts legal and ethical perspectives to analyze the subject and the subjective, incidence, and sentencing factors of wildlife crimes and uses the ecological economic ethical model to measure wildlife crimes. We argue that the existing judicial system fails to answer the difficulties of the economic ethics of wildlife crimes. It is recommended that ecological and economic ethical awareness be internalized. We suggest calling for comprehensive legislation on wildlife crimes from the perspective of ecological economic ethics to effectively prevent and reduce wildlife crime and eventually promote public health.